Customary Payment to Achieve A Justice in The Land Disputes - Marlin Marlin; Farida Patittingi; Suriani BT Tolo (Al-'Adl, 2021)
The indigenous people of South Konawe highly uphold the Tolaki customary law from ancient times to the present, namely through the Kalosara media, which is considered very sacred to its existence. Land dispute resolution through customary payment has a purpose to restore disturbed conditions caused by the disputing parties. This research examines and describes the implementation of customary payments for land disputes, whether it can fulfill a sense of justice for the indigenous people of South Konawe. The research uses some secondary data through literature studies and primary data through the interview. The result indicates that the customary payment in giving a sense of justice in land disputes in South Konawe is considerably applicable. However, a comprehensive study is needed to find the justice which is aspired by the Tolaki Indigenous People in South Konawe.